MENTAL HEALTH GURU PAUD (TELAAH LITERATUR KUALITATIF TERHADAP FAKTOR RISIKO DAN STRATEGI PEMULIHAN) - Permatasari, Tisya (Pusat Penelitian dan Pengabdian kepada Masyarakat STKIP Citra Bakti, 2025)
The mental health of Early Childhood Education (ECE) teachers is a fundamental aspect that directly influences the quality of caregiving, educational interactions, and the creation of a warm and safe learning environment for children in their golden age. ECE teachers not only serve as educators but also as caregivers and facilitators of children’s socio-emotional development. However, the high professional demands, excessive administrative workload, and lack of psychosocial support often generate significant pressure on teachers’ mental well-being. This study aims to qualitatively examine reputable scientific literature discussing the risk factors and recovery strategies related to the mental health of ECE teachers. Data were obtained through an exploration of scholarly articles using Publish or Perish software and bibliometric analysis via VOSviewer, applying inclusion criteria of reputable national and international journals published between 2020 and 2025. A total of 25 articles were selected and analyzed using a systematic literature study approach. The review reveals that work stress, administrative burden, low professional recognition, and job insecurity are dominant factors affecting ECE teachers’ mental health. Meanwhile, effective recovery strategies include individual approaches (mindfulness, stress management, and emotional regulation), institutional approaches (social support, supportive supervision, and wellbeing training), and policy approaches (improving welfare and providing counseling services for teachers). These findings highlight the importance of synergy among individuals, institutions, and policymakers in promoting sustainable mental health for ECE teachers to enhance the quality of early childhood education. Keywords: mental health, early childhood teachers, work stress, recovery strategies.